PELATIHAN KETERAMPILAN TANGAN BERBAHAN DASAR KAIN FLANEL PADA ANAK USIA DINI DI DESA LUBANG BUAYA - Setiawati, Eris; Sikki, M. Ilyas; Supratno, Setyo (An-Nizam, 2025)
The development of fine motor skills in early childhood plays a crucial role in fostering creativity, enhancing hand coordination, and building children’s self-confidence. This community service program was conducted in Lubang Buaya Village with the primary objective of improving children’s manual skills through practice-based training. The applied method consisted of initial observation to identify needs, training sessions, and hands-on practice in producing creative works. The main material used in this activity was flannel fabric, with the final product being a handmade keychain. A total of 21 early childhood participants were actively engaged throughout the implementation process. The results demonstrated that the training effectively improved children’s fine motor skills, strengthened their creativity, and enhanced their confidence in appreciating their own work. The children were able to produce simple yet meaningful creations and showed high enthusiasm during each session. Therefore, flannel-based handicraft training proved to be an effective method for empowering early childhood development and contributed significantly to nurturing children’s potential in Lubang Buaya Village.